PENERAPAN STRATEGI PEMBELAJARAN KOOPERATIF PADA PELAJARAN PRODUKTIF TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA KELAS XII PMS 2 SMKN I LUMAJANG - Cholid Musmudi (FKIP Universitas Islam Jember, 2015)
Curriculum 2004 highly requires the students to have critical thinking skills. At this juncture, learning strategies in improving students’ creative thinking skills arevery important. Therefore, this study needs to produce an innovative learning strategy through the implementation of cooperative learning in developing students’ creative thinking skills. In this study, the researcher employed classroom action research (CAR) as the research design in which the researcher carries out the cyclical procedure of the study: planning, implementing, observing, and reflecting on the action. This cyclical procedure is implemented on the subject of how to operate communication equipment. This study, which took three cycles, was conducted in class XII PMS 2 in SMKN Lumajang. The findings of this study revealed that cooperative learning strategy can improve the students’ creative thinking skills as their final score on the third cycle exceeded the criteria of minimum completeness (KKM). With the lowest score of 80 and the highest one of 100, the students were regarded to have “good” creative thinking skills. In reference to the result of the study, therefore, it can be concluded that through the implementation of cooperative learning, the students can improve their creative thinking skills shown by their achievement score which have significantly increased.Keywords: Cooperative, creative thinking.